(untitled) (Palimpsesto, 2017)
This article proposes approaches to the history of Quillagua Valley – and its population – between the XVI and the XX centuries. This will be done based on three core questions: what happened in Quillagua Valley since the Hispanic Conquest? What happened to the lands where indigenous people lived? What happened to the indigenous population? The investigation strategies used are varied. On the one hand, there is a collection of archaeological, ethnohistorical, and historical information. On the other hand, we used oral history to account for the memories of the inhabitants. These are ways of approaching that have allowed for understanding historical transitoriness, which has been marked not only by change and transformation processes but by continuity, as well.